First Person Acting on Second Person in Maliseet - Szabó, László (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1997)
One can say in English “I see you,” “we see you”. We can make similar statements using past tense or a few other forms of the verb. The number of our possible verb forms is significantly higher in the Maliseet equivalents of these sentences. Four possibilities are shown by our arrows: I —–> Thee I —–> you (plural) we —–> Thee we —–> you (plural) In the Maliseet transitive animate verb inflection these forms are different in the independent indicative from the forms in the conjunct order. This fact gives us eight potential forms instead of four. Theoretically, each of them can be used with future, conditional, conclusive or past enclitic, or even with the combination of the conclusive and the past enclitic. This gives us five times eight, i.e. forty possibilities. In negation the negative final causes serious changes in the verb inflection. This means that we can expect eighty forms instead of forty. This number goes still higher if we use some additional devices, for instance, the real plural markers to distinguish between duality and plurality. The use of the relative final can give us some additional forms as well. I noted down 5,000 pages of Maliseet Stories, on the basis of oral story telling in Maliseet. I take examples from my huge Maliseet text collection, and try to answer this question: How many ending combinations are there in 500 pages of stories, about a tenth of my collection, in the “I...you” expressions in this Indian language?